Synthesis and study of complexes of the novel Russian antiviral drug Camphecene with Plant’s Flavonoids - S. S. Khizrieva; E. V. Vetrova; S. N. Borisenko; E. V. Maksimenko; N. I. Borisenko (Chimica Techno Acta)
Traditionally, glycyrrhizic acid has been used to form polydentate complexes. For the first time in the presented paper, the complexation of the Plant’s Flavonoids (Quercetin (Qu) and its glycoside - Rutin (Rut)) with the novel Russian antiviral drug Camphecene (Camph) was investigated. The complexes obtained at different molar ratios were studied using UV/Vis spectroscopy. Formation of the host: guest complexes were registered: Qu and Rut molecular complexes (Camph+2Qu; Camph+2Rut) with a stability constant K = 3.3·108 M-2. Comparison of the binding constants of the obtained complexes shows that the efficiency of Camphecene complexation with the participation of flavonoids is more efficient than with the participation of triterpenoids. Besides, it was found that the complexes of Camphecene with the quercetin and rutin are soluble in water, in contrast to the complexes with triterpenoids, which makes it possible to increase the bioavailability of both Camphecene and flavonoids. The obtained results demonstrate the high potential of flavonoids Qu and Rut to the development of novel pharmaceutical forms using the example of Camphecene in the form of molecular complexes, as the novel forms of delivery.